2020
DOI: 10.1111/vsu.13380
|View full text |Cite
|
Sign up to set email alerts
|

Sterility and concentration of liposomal bupivacaine single‐use vial when used in a multiple‐dose manner

Abstract: Objective: To evaluate the sterility of bupivacaine liposome injectable suspension (Nocita ® ) used in a multiple-dose fashion for 5 days.Study design: Triplicate liposomal bupivacaine vials were stored under two conditions, (1) room temperature (24 C) and (2) refrigerated temperature (5 C). A 3-mL aliquot was withdrawn from each vial daily. Samples were inoculated in tryptic soy broth in triplicate and then incubated for 24 hours at 37 C and subcultured every 48 hours onto blood agar and Sabouraud dextrose ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 10 publications
0
9
2
Order By: Relevance
“…The reported concentration of free bupivacaine in liposomal bupivacaine suspensions is 1.064 mg/mL, 22 which is less than the free bupivacaine concentrations in any of our samples, including the control (1.90 mg/mL). Carlson et al 22 found an average of 1.2 mg/mL when they assayed free bupivacaine concentration using the same method we used. However, their samples were taken from the liposomal bupivacaine vial and immediately processed on site.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…The reported concentration of free bupivacaine in liposomal bupivacaine suspensions is 1.064 mg/mL, 22 which is less than the free bupivacaine concentrations in any of our samples, including the control (1.90 mg/mL). Carlson et al 22 found an average of 1.2 mg/mL when they assayed free bupivacaine concentration using the same method we used. However, their samples were taken from the liposomal bupivacaine vial and immediately processed on site.…”
Section: Discussioncontrasting
confidence: 63%
“…All samples were stored, prepared, and analyzed as described by Carlson and colleagues 22 . Liposomal bupivacaine samples were centrifuged at 3500 g for 30 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in a decrease in colony survival similar to that in SFB. The short-term lack of toxicity may be related to the low concentration of free bupivacaine achieved by using LEB (approximately 1.2 mg/mL 23 ). In an in vitro study, Shaw et al 16 treated bovine chondrocytes with LEB for 1 hour and found no difference compared with saline and a significant difference from 5 mg/mL SFB when evaluated by using flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…This was to better emulate clinical use of a 10‐fold dilution of stock bupivacaine and because no difference was seen between 0.4 and 0.6 mg/mL SFB according to MTT assay (Table 1). Undiluted LEB is expected to result in a free bupivacaine concentration of approximately 1.2 mg/mL, 23 and the product label allows for dilution of up to 50% by volume when saline is used 24 . All dilutions of bupivacaine were performed with 0.9% saline.…”
Section: Methodsmentioning
confidence: 99%